Antibacterial activity of Nigella sativa against multi-drug resistant bacteria - Arooba Khalid ,; Syed Sohail Ahmad, (International Journal of Pathology, 2024)
Background: Multidrug Resistant (MDR) bacteria are considered as the one of the most dangerous pathogens causing a high mortality rate globally. Medicines from the natural source might be the best therapeutic option in current emerging trends of resistance. Methods: We determined the antibacterial activity of Nigella sativa seeds extracts against the clinical isolates of MDR Staphylococcus aureus and Escherichia coli. The collection of different isolates was done from the different hospitals’ settings in Faisalabad. Identifications of these isolates were done phenotypically and through the conventional PCR via genus and species-specific primers. The isolates were then tested for antimicrobial susceptibility using agar well diffusion technique. The activity of N. sativa seed oil was also evaluated in DMSO at concentrations (25%, 50% and 75%). Results: Against S. aureus, 50% oil concentration in DMSO exhibited highest inhibitory zone of 15 mm followed by 90% ethanol extract showed clear zone of 13 mm and 12 mm zone of inhibition showed by the methanol-based extract. Against E. coli 50% oil concentration in Dimethyl sulfoxide (DMSO) and 90% ethanol extract both showed clear zone of 12 mm and 11 mm zone of inhibition showed by the methanol-based extract. However, Minimum inhibitory concentration (MIC) of 50% oil concentration is 0.4 μl followed by 90% ethanol extract showed 0.4 mg and 0.8 mg showed by the methanol-based extract 90% on S. aureus. The oil concentration MIC value of 50% is 0.4 μl then followed by the ethanol extract at 90% and revealed 0.4mg and methanol was followed by 90% extract showed 0.4 mg to the E. coli. Conclusion: We concluded that N. sativa can be used as a pharmaceutical and new therapy for action against MDR bacteria.